DESIGN OF AUTOPILOT TRACKING CONTROL AT A PROTOTYPE TANK BASED ON ARDUINO - Sunarta Sunarta; I Nengah Putra A; Cucuk Wahyudianto; Muhammad Husni Afandi (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
The Indonesian Navy is one elements of the Indonesian nation which has the duty to maintain the unity andunity of the Republic Indonesia. The Indonesian Navy requires a lot of equipment, defense equipment andsupporting equipment. Unmanned Tank Alutsita is one vehicle that can be used as a combat vehicle withoutinvolving troop personnel in the tank that can be controlled remotely through wireless data communication. Thedesign of the location-based prototype tank autopilot control system is a research in answering for thedevelopment of unmanned warfare technology. Prototype unmanned tank using GPS sensor bases, imu andcompass determining the location, orientation and direction of the prototype. The application of the compass asan evaluation of the tank bow course error towards the direction of the destination, while GPS is used as aparameter for determining the location of the destination location. The combination of the two sensors is usedas a base information on the control system on autopilot. From the results of tests that have been carried outobtained manual control systems and autopilot in accordance with the itinerary that has been made. The vehicletank can respond in real time to any location and direction errors, so that corrections can be made to reach thedestination correctly. Weather problems become a barrier factor in getting location data from GPS. During thetest in sunny conditions obtained control results with a location error factor of less than 5 meters.Keyword : Prototype, control, autopilot